Evaluation of Response to Therapy in a Patient with Lung Cancer: Correlation of Sclerotic Bone Lesions with F 18 FDG PET/CT and Bone Scintigraphy - Özülker, Tamer (Galenos Publishing, 2011)
A 64-year-old male patient with small cell lung cancer underwent Fluorine-18 fluorodeoxyglucose (F 18 FDG) positron emission tomography (PET)/CT scan which revealed multiple F 18 FDG uptake in the spine, both humeri, ribs, pelvis and proximal long bones. There was no obvious lytic or sclerotic bone destruction accompanying these lesions on CT component of the study. After the patient received six courses of chemotherapy a repeat F 18 FDG-PET/CT was performed for evaluation of therapy response. The PET/CT showed the presence of multiple sclerotic lesions on CT without FDG uptake, corresponding to the bone lesions on the previous PET/CT scan. A concomitant Tc 99m Methylene diphosphonate (Tc 99m MDP) bone scintigraphy (BS) revealed no pathologically increased Tc 99m MDP uptake in the skeletal system. The FDG avid lesions in the skeletal system, which were not sclerotic initially, were transformed into FDG non-avid sclerotic lesions after chemotherapy. This was attributed to the direct effect of previous successful therapy for bone metastases, leading to the transformation of metabolically active disease, into blastic metabolically inactive metastases. In conclusion, a F 18 FDG negative bone lesion, which is sclerotic on CT, may represent post-treatment osteoblastic change rather than active tumor and BS might play a role in the discrimination of these two situations. Conflict of interest:None declared.